Neutral tritium gas reduction in the KATRIN differential pumping sections. (February 2021) - Marsteller, A.; Bornschein, B.; Bornschein, L.; Drexlin, G.; Friedel, F.; Gehring, R.; Grohmann, S.; Gumbsheimer, R.; Hackenjos, M.; Jansen, A.; Kosmider, A.; La Cascio, L.; et al.
Abstract: The KArlsruhe TRItium Neutrino experiment (KATRIN) aims to measure the effective electron anti-neutrino mass with an unprecedented sensitivity of 0.2 eV/c 2, using β -electrons from tritium decay. The electrons are guided magnetically by a system of superconducting magnets through a vacuum beamline from the windowless gaseous tritium source through differential and cryogenic pumping sections to a high resolution spectrometer and a segmented silicon pin detector. At the same time tritium gas has to be prevented from entering the spectrometer. Therefore, the pumping sections have to reduce the tritium flow by more than 14 orders of magnitude. This paper describes the measurement of the reduction factor of the differential pumping section performed with high purity tritium gas during the first measurement campaigns of the KATRIN experiment. The reduction factor results are compared with previously performed simulations, as well as the stringent requirements of the KATRIN experiment. Highlights: Measurement of tritium gas flow reduction in differential pumping in KATRIN. Reduction of gas flow by more than 7 orders of magnitude. Excellent agreement between measurement and simulations. Regeneration interval of KATRIN cryogenic pump longer than 60 days possible.